Virtualizing the fundamental aspects of ‘Al-Wasatiyyah’: an exploratory revision - Yaakub, Muhamadul Bakir; Othman, Khatijah (Medwell, 2018)
This is an exploratory study on the terminological term of ‘al-Wasatiyyah’. It is an attempt to examine the term in a comprehensive and practical manner within the current context. The issue is crucial since the term ‘al-Wasatiyyah’ epitomizes the current Malaysian’s governmental policy, where ‘al-Wasatiyyah’ been declared as its socio-political landmark in facing today’s complexities and dynamic changes. The international political and security situation can change dramatically without any warning. The task of managing foreign policy has become equally difficult. It calls for a more pragmatic, flexible and compromise approach. This can be achieved through analysing its utilization as per its original resources in the Glorious Quran and the Prophetic tradition. The main finding revealed that the term remains an important counterpoint to structural explanation on interpersonal understanding and socio-cultural engagements within human socio-cultural perspective in the form of clear functional characteristics.